On a Quantitative Method in Production Planning and Scheduling - Salveson, Melvin E. (Econometrica, 1952)
Definitions and axioms based on engineering and economic concepts in production are presented, and then a conceptual model of production is constructed illustrating the methods which the manager uses in planning and scheduling production. Even under the assumed conditions of certainty in demand and prices, it is shown to be a difficult task and one in which optimal solutions are seldom achieved. In order then to indicate the relevance of the model and its eventual possible usefulness, it is compared with industrial practices and with other mathematical models of production.